Harnessing Fiber Diameter-Dependent Effects of Myoblasts Toward Biomimetic Scaffold-Based Skeletal Muscle Regeneration - Narayanan, Naagarajan; Jiang, Chunhui; Wang, Chao; Uzunalli, Gözde; Whittern, Nicole; Chen, Da; Jones, Owen G.; Kuang, Shihuan; Deng, Meng (Frontiers in Bioengineering and Biotechnology, 2020)
Regeneration of skeletal muscles is limited in cases of volumetric muscle loss and muscle degenerative diseases. Therefore, there is a critical need for developing strategies that provide cellular and structural support for skeletal muscle regeneration. In the present work, a bioengineered cell niche composed of mechanically competent aligned polyester fiber scaffolds is developed to mimic the oriented muscle fiber microenvironment by electrospinning poly(lactide-co-glycolide) (PLGA) using a custom designed rotating collector with interspaced parallel blades. Aligned fiber scaffolds with fiber diameters ranging from 335±154 nm to 3013±531 nm are characterized for their bioactivities in supporting growth and differentiation of myoblasts. During in vitro culture, polymeric scaffolds with larger fiber diameter support enhanced alignment, growth, and differentiation of myoblasts associated with phosphorylation of p38 MAPK and upregulated expression of myogenin and myosin heavy chain. In vivo studies using a dystrophin-deficient mdx mouse model show that optimized fiber scaffolds seeded with primary myoblasts result in formation of dystrophin-positive myofibers network in tibialis anterior muscles. Collectively, these set of experiments provide critical insights on harnessing interactions between muscle cells and engineered fiber matrices to develop effective biomaterials for accelerated muscle regeneration.